Revolutionizing Education: 10 Innovative Teaching Strategies for the 21st-Century Classroom - Sabrifha, Eli; Wasari, Retno; Mokoena, Thabo (CV Berkah Syahdin Trust, 2025)
The rapid evolution of technology and shifting educational demands necessitate transformative teaching strategies to enhance student engagement, critical thinking, and lifelong learning in 21st-century classrooms. Traditional pedagogical approaches often fail to address diverse learning needs, calling for innovative solutions. This study identifies and evaluates 10 innovative teaching strategies designed to modernize education, focusing on their applicability, effectiveness, and impact on student outcomes. A systematic literature review was conducted, analyzing peer-reviewed articles (2015–2024) from Scopus and Web of Science databases. Data were synthesized to compare strategies like flipped classrooms, gamification, project-based learning (PBL), and microlearning, with empirical evidence from global case studies. The findings reveal that strategies such as blended learning, inquiry-based learning, and design thinking significantly improve student motivation, collaboration, and problem-solving skills. Technology-integrated methods (e.g., AI tools, VR) show promise but require infrastructure and teacher training. Contextual adaptability and teacher readiness emerged as critical success factors. To revolutionize education, educators must adopt flexible, student-centered strategies while addressing implementation barriers. Policymakers should support professional development and resource allocation to sustain these innovations.